2012
DOI: 10.1111/j.1758-8111.2012.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipedema: an overview of its clinical manifestations, diagnosis and treatment of the disproportional fatty deposition syndrome – systematic review

Abstract: Lipedema is a disproportionate, symmetrical fatty swelling characterized by pain and bruising existing almost exclusively among women. We undertook a systematic review of the available literature about lipedema, given the lack of knowledge and little evidence about this disorder especially among obesity experts. Diagnosis of lipedema is usually based on clinical features. Symmetrical edema in the lower limbs with fatty deposits located to hips and thighs usually appears at puberty and often affects several mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
1
18

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 32 publications
1
135
1
18
Order By: Relevance
“…Lipedema typically develops after puberty and predominantly occurs in females. Divergent prevalence estimates exist due to various factors, such as whether patients were identified in the general population or in a specialty clinic [Child and others 2010; Fife and others 2010; Forner-Cordero and others 2012]. Currently, the etiology of lipedema is unknown, but familial clustering is noted and mechanistic hypotheses include impaired estrogen signaling and microangiopathy due to endothelial barrier dysfunction [Szel and others 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Lipedema typically develops after puberty and predominantly occurs in females. Divergent prevalence estimates exist due to various factors, such as whether patients were identified in the general population or in a specialty clinic [Child and others 2010; Fife and others 2010; Forner-Cordero and others 2012]. Currently, the etiology of lipedema is unknown, but familial clustering is noted and mechanistic hypotheses include impaired estrogen signaling and microangiopathy due to endothelial barrier dysfunction [Szel and others 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, according to a study of Foldi et al, prevalence of lipedema was up to 11% among women and postpubertal girls in their test group [4]. Forner-Cordero et al reported 18.8% of the patients in their unit with enlargement of the lower limbs between 2005 and 2012 [5]. Among patients hospitalized for lymphatic disease, the proportion is estimated as 8-17% [6].…”
Section: Epidemiology Of Lipedemamentioning
confidence: 97%
“…Occasionally, medications can also be considered: beta-adrenergic agonist for capillary leak syndrome, glucocorticosteroids for swelling and pain, cimetidine and beta glucan to improve the impaired local immune response due to edema [12], short-course of diuretics or selenium for lipedema with concomitant lymphedema [13]. Decongestive lymphatic therapy including manual lymphatic drainage, physical exercise, multilayered and multicomponent compression bandaging and meticulous skin care is the standard conservative approach for lipedema treatment [5]. Complex form of this decongestive lymphatic therapy has also been shown to decrease bruising, one of the hallmarks of lipedema [14].…”
Section: Therapeutical Approachesmentioning
confidence: 99%
“…For example, exploring claims that an adjustable compression wrap works in a similar way to an inelastic bandage system. 10,11 Further work is required to evaluate and contrast the effect of the products with different groups: for example, individuals who undergo liposuction for lymphoedema or lipoedema 39 ; or in people with different skin and tissue conditions such as the soft pliable tissues in someone with lipoedema, and the hard fibrotic tissues characteristic of late stage lymphoedema. 40 Selfmanagement remains poorly understood and researched 41 , so further work is required to ensure practitioners and patients have appropriate support with new and different ways of working with patients, and are familiar with the various key aspects of self-management that complement the use of an adjustable compression wrap device.…”
Section: Recommendationsmentioning
confidence: 99%